2021
DOI: 10.1136/annrheumdis-2021-220781
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 vaccination in rituximab-treated patients: B cells promote humoral immune responses in the presence of T-cell-mediated immunity

Abstract: ObjectivesEvidence suggests that B cell-depleting therapy with rituximab (RTX) affects humoral immune response after vaccination. It remains unclear whether RTX-treated patients can develop a humoral and T-cell-mediated immune response against SARS-CoV-2 after immunisation.MethodsPatients under RTX treatment (n=74) were vaccinated twice with either mRNA-1273 or BNT162b2. Antibodies were quantified using the Elecsys Anti-SARS-CoV-2 S immunoassay against the receptor-binding domain (RBD) of the spike protein and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
245
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 226 publications
(311 citation statements)
references
References 30 publications
38
245
3
4
Order By: Relevance
“…In contrast, none of the patients in our study had detectable anti-SARS-CoV-2 antibodies at baseline. Detectable peripheral B-cells serve as a key factor for seroconversion in rituximabtreated patients 14 and randomization was therefore stratified by presence or absence of peripheral B-cells. As described after conventional vaccination with two mRNA vaccine doses, presence of detectable peripheral B-cells was the strongest determinant for seroconversion also in patients receiving an additional booster vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, none of the patients in our study had detectable anti-SARS-CoV-2 antibodies at baseline. Detectable peripheral B-cells serve as a key factor for seroconversion in rituximabtreated patients 14 and randomization was therefore stratified by presence or absence of peripheral B-cells. As described after conventional vaccination with two mRNA vaccine doses, presence of detectable peripheral B-cells was the strongest determinant for seroconversion also in patients receiving an additional booster vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Data were calculated as spot-forming cells (SFCs) per 10 6 PBMCs after subtracting of the spots from the negative control (mean spot numbers from three to four unstimulated wells). T-cell responses were considered positive if spot counts were greater than the mean SFCs plus three times the standard deviation from pre-pandemic controls, as defined previously 14 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most immunosuppressive drugs appear to have moderate to no effect on immunogenicity. However, drugs like Rituximab have also been shown to be associated with lower rate of seroconversion post-vaccination[15]. We have previously shown that patients on immunosuppressive therapy respond similarly to the healthy controls following SARS-CoV-2 infection[16].…”
Section: Introductionmentioning
confidence: 99%